Culture and terrorism: the role of cultural factors in worldwide terrorism (1970-2013) - Pinero Kluch, Sofia (Terrorism and political violence, 2017)
The relationship between terrorism and culture was systematically examined using three high-quality global databases. Contrary to prior research, terrorism—collapsed across form and era—was not related to any of Hofstede's cultural dimensions. Yet, particular forms of terrorism—incidents involving substantial casualties and damage, suicide bombings, and the proportion of incidents involving fatalities—all showed relationships with cultural dimensions. Tolerance of terrorism and relative tolerance of the 9/11 attack were related to cultural dimensions and terrorist events. Finally, populations that were relatively voiceless, disengaged from their communities, suffering, angry, and hopeless showed more tolerance of terrorism and incidents of terrorism.